Effectiveness of an Informative Website on Behavioral Determinants of Community-Based Total Sanitation for Stunting Prevention: A True Experiment - Ratna Dian Kurniawati; Suherdin Suherdin; Yosef Pandai Lolan (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Stunting is a persistent nutritional problem that impacts children's growth and development, as well as the quality of future human resources. The stunting rate has not yet reached the national target. The informative website, the Libas Stunting Education System (SiEduk), focuses on implementing the five pillars of Community-Based Total Sanitation (STBM) to prevent stunting. This study aims to analyze the effectiveness of the informative website SiEduk Libas Stunting in Bandung Regency. Methods: This quantitative research employed a purely experimental research design with a pretest-posttest control group design. The study was conducted from July to December 2025. The research sample consisted of 700 housewives and was taken randomly. Simple Random Sampling based on inclusion and exclusion criteria then divided into experimental group and control group. Data were collected from a questionnaire that had been tested for validity and reliability. Data analysis was performed using an independent t-test. Data came from pre-test and post-test questionnaires. Ethical approval from the ethics committee of Bhakti Kencana University with number 211/09.KEPK/UBK/VII/2025. Results: There were significant differences between the intervention and control groups in all variables studied, with a P value <0.001. The knowledge variable showed the highest increase with an average difference of 0.771, followed by perception at 0.371, attitude at 0.314, and motivation at 0.257. These results indicate that digital education through the informative website SiEduk Libas Stunting is effective in increasing the understanding and implementation of Community-Based Total Sanitation. Conclusion: Digital-based informative websites like SiEduk Libas Stunting have proven effective in improving the knowledge, attitudes, perceptions, and motivation of housewives to implement the Five Pillars of Community-Based Total Sanitation to prevent stunting. Support from the Health Office and cross-sectoral collaboration are needed to maximize public access to the informative website.